The Contribution of Managerial Ability and Entrepreneurial Motivation on Business Performance with Business Climate as Mediation Variable - Salim Al Idrus; Absussakir Abdussakir; Shofiyah Al Idrus; Ansari Saleh Ahmar (Fakultas Ekonomi, UIN Maliki Malang, 2022)
The national economics were horribly unsettled by covid-19 pandemic. Domestic consumption level fell sharply because the long post-pandemic recovery had severely impacted production and trade sectors where Small and Medium Enterprises do business most. Unhealthy business climate becomes pivotal moment for academicians to review the capability of Small and Medium Enterprises to survive the effect of covid-19 pandemic. The review was carried out by analyzing the contribution of managerial ability and entrepreneurial motivation to business performance through the mediation of business climate. East Java was selected as the scope of research. Number of sample was 120 Small and Medium Enterprises sorted with purposive sampling. Primary data were obtained through questionnaire. Analytical method was Partial Least Square operated with SmartPLS. Result of research showed that the significant impact of managerial ability and entrepreneurial motivation on business performance has made Small and Medium Enterprises consider as necessary to improve the potential and effectiveness of business management that has been applied. The situation of covid-19 pandemic also compelled Small and Medium Enterprises to strengthen entrepreneurial motivation to keep business performance increasing.